Memahami Kemukjizatan Al-Qur’an - Rais Abdurrahman Siregar; Milhan Milhan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The Qur'an is the greatest miracle received by the Prophet Muhammad. The miracle of the Qur'an is commonly referred to as I'jaz Al-Qur'an. The miracle of the Qur'an is a term that arises in response to the inability of humans to match the beauty of the language and the message contained in it. Sunni scholars believe that the miracle of the Qur'an comes from itself, while Muktazilah scholars argue that the inability of humans to match the Qur'an is due to al-sarfah (transfer / revocation) of the ability by Allah swt. to match the Qur'an. This study aims to determine the meaning of the Miracle of the Qur'an, the dimensions of the Qur'anic Miracle, and the direction of the Qur'anic Miracle study. This research uses library research method. The results showed that a miracle according to M. Quraish Shihab is an extraordinary thing or event that occurs through someone who claims to be a prophet, as proof of his prophethood which is challenged to people who doubt, to do or bring similar things, but they are unable to meet the challenge. The dimensions of the Qur'ān are divided into several aspects, namely in terms of preaching and linguistic aspects. And now there is a new direction in understanding the miracle of the Qur'an, namely in terms of science and technology.